Identitas Budaya Konsumerisme dalam Film Orang Kaya Baru oleh Ody Harahap : (Kajian Psikologi Konsumerisme Abraham Maslow) - Lailatul Fitriyah; Hurriana Hurriana; Mahbubi Mahbubi; Ilyas Ilyas; Muhammad Alfirdaus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the phenomenon of consumerism that emerges in the modern era. The culture of consumerism is embodied in the film “Orang Kaya Baru” by Ody Harahap (2019). In today's era, with rapid technological advancements, there has been a trend of lifestyles that contribute to the formation of consumer culture. Consumerism has become an inseparable part of society, ultimately impacting individual psychology in fulfilling needs. This research utilizes Abraham Maslow's hierarchy of needs theory as a reference and benchmark for the obtained data. This article analyzes how the change in the Wardana family's economic status from modest to wealthy leads to drastic changes in the family's consumerist behavior. The research method used is qualitative, focusing on scene transcripts or dialogues in the film to identify excessive consumerist behavior and its impact on their family relationships. The results of the analysis show that before becoming wealthy, the Wardana family was able to meet their basic needs adequately. However, after receiving a large inheritance, they became trapped in excessive consumerist behavior, leading to a neglect of the difference between needs and wants.